Parallel world hypotheses in physics - Kostandov, T. A. (ТДАТУ, 2020)
Modern science has quite a sphere of action. On the other hand, people know too little to make hasty conclusions based on sensational hypotheses and theories.
Keywords: problem of parallel worlds; interpretation; electrons in a planetary system